The Effect of Aloe Vera (Aloe barbadensis Miller) Extract on the Number of Inflammatory Cells (Neutrophils and Macrophages) in the Gingivitis Model (Rattus norvegicus) Wistar Rat Model - Netta Anggraini; Refika Ananta; Fauzia Nilam Orienty (Interdental Jurnal Kedokteran Gigi (IJKG), 2026)
Introduction: Gingivitis is an inflammatory gingival disease associated with local factors, medication use, and malnutrition. Aloe vera (Aloe barbadensis Miller) contains flavonoids, tannins, saponins, polyphenols, and steroids with potential anti-inflammatory effects. This study aimed to determine the effect of aloe vera extract at concentrations of 50%, 75%, and 100% on neutrophil and macrophage counts in a gingivitis model of male Wistar rats. Materials and Methods: This laboratory experimental study used a posttest randomized controlled group design involving 48 male Wistar rats divided into four groups: negative control and gingivitis groups treated with 50%, 75%, or 100% aloe vera extract. The extract was applied topically to the mandibular anterior gingiva twice daily for five days. Tissue samples were collected on days 3 and 5 and stained with hematoxylin and eosin. Data were analyzed using two-way ANOVA and Bonferroni tests (p<0.05). Results and Discussion: Topical aloe vera extract significantly reduced inflammatory neutrophil and macrophage counts (p<0.001). On day 5, mean neutrophil counts were 0.67, 0.17, and 0 cells/mm³ in the 50%, 75%, and 100% groups, respectively. Mean macrophage counts were 1, 0.3, and 0 cells/mm³, respectively. Conclusion: Topical aloe vera extract demonstrated anti-inflammatory activity, with 75% and 100% concentrations being the most effective in reducing inflammatory cell counts in gingivitis.